The family Lohmanniidae (Acari, Oribatida) II: two new Oribatid mites, Meristacarus perikopesis sp. n. from Costa Rica and Torpacarus eidikoterai sp. n. from Kenya - Fernandez, Nestor (2018)
Two very particular new species of the family Lohmanniidae were studied and described using optical and Scanning Electron Microscopy (SEM). Meristacarus perikopesis sp. n. displays complex cuticular microsculpture with cross-shaped grooves and pusticulate porose areas; ten transversal bands, with reticulate-foveate microsculpture; S4, S5, S7, S10 not crossing medial notogastral plane, amongst other characters. Torpacarus eidikoterai sp. n. with: prodorsum - rostrum weakly bilobate with small central structure and CSO present. Six transversal depressions present, transversal bands absent; but six transversal depressions present, none of the depressions crossing medial notogastral plane.